Portrayed of Nature Philosophy Through Japanese Cinema: Representation of Nihonjin no Shizenkan in Sweet Bean Movie - Sari, Rima Novita; Pamugari, Alpina (Universitas Negeri Semarang, 2024)
This study analyzes how Japanese people love nature, as presented in the movie Sweet Bean. Nihonjin no shizenkan is considered one of the Japanese ideal philosophies for valuing nature. The artwork sometimes portrays the abstract concept and how people adore their environment. This study examines the depiction of nihonjin no shizenkan philosophy in contemporary Japanese society, exemplified by the 2015 movie Sweet Bean. The data were gathered using a qualitative approach and the content analysis technique. The theory employed is the shizenkan no kyouiku concept, demonstrated by Sugai Hiroyuki, which refers to the people's way of life to seeing and value nature by heart, represented by back to nature, being one with and an act to respect nature. The film demonstrates that individuals in Japan, limited to their age, continue to practice nihonjin no shizenkan, which is presented by viewing nature as friends or a living thing. Based on the data, we split into two categories: (1) a person can communicate or interact with nature, and (2) see nature material as a living thing. The movie concludes that the interaction between people and nature significantly impacts someone's life and gives influence on businesses. This study can show how the Japanese value nature and any further cultural understanding.